Pelatihan Pembelajaran dari Rumah dalam Rangka Menghadapi Pandemi Covid 19 pada Guru-Guru SD Kota Metro - Supriyadi; Ika Wulandari Utamining Tias; Frida Destini; Amrina Izzatika (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS LAMPUNG, 2023)
One of the problems currently being faced by the Indonesian state is education which must continue in the midst of the Covid-19 pandemic. Direct or face-to-face learning cannot be carried out because there is a government policy to implement physical distancing, and requires the learning process to be carried out at home. Learning from home through online/distance learning is carried out to provide a meaningful learning experience for students, without being burdened with the demands of completing all curriculum achievements for grade promotion and graduation. Learning from home learning activities and tasks may vary between students, according to their individual interests and conditions, including considering the gap in access/facilities for learning at home. Service activities carried out with the aim of understanding and knowing what and how to learn from home during the pandemic and understanding the implementation of fun learning from home. The targets are elementary school teachers located in Metro City. The method used is the lecture method, question and answer method, and the method of giving examples. The expected condition after this service is an increase in teacher understanding and knowledge about what and how to learn from home that is fun and can provide a learning experience for students.